Enhanced Hepatogenic Transdifferentiation of Human Adipose Tissue Mesenchymal Stem Cells by Gene Engineering with Oct4 and Sox2 - Han, Sei-Myoung (PLoS One, 2015)
Adipose tissue mesenchymal stem cells (ATMSCs) represent an attractive tool for the establishment of a successful stem cell-based therapy in the field of liver regeneration medicine. ATMSCs overexpressing Oct4 and Sox2 (Oct4/Sox2-ATMSCs) showed enhanced proliferation and multipotency. Hence, we hypothesized that Oct4 and Sox2 can increase “transdifferentiation” of ATMSCs into cells of the hepatic lineage. In this study, we generated Oct4- and Sox2-overexpressing human ATMSCs by liposomal transfection. We confirmed the expression of mesenchymal stem cell surface markers without morphological alterations in both red-fluorescent protein (RFP) (control)- and Oct4/Sox2-ATMSCs by flow cytometry. After induction of differentiation into hepatocyte-like cells, the morphology of ATMSCs changed and they began to appear as round or polygonal epithelioid cells. Hepatic markers were evaluated by reverse transcription-polymerase chain reaction and confirmed by immunofluorescence. The results showed that albumin was strongly expressed in hepatogenic differentiated Oct4/Sox2-ATMSCs, whereas the expression level of α-fetoprotein was lower than that of RFP-ATMSCs. The functionality of hepatocytes was evaluated by periodic acid-Schiff (PAS) staining and urea assays. The number of PAS-positive cells was significantly higher and urea production was significantly higher in Oct4/Sox2-ATMSCs compared to that in RFP-ATMSCs. Taken together, the hepatocyte-like cells derived from Oct4/Sox2-ATMSCs were mature hepatocytes, possibly functional hepatocytes with enhanced capacity to store glycogen and produce urea. In this study, we demonstrated the enhanced transdifferentiation of Oct4- and Sox2-overexpressing ATMSCs into hepatocyte-like cells that have enhanced hepatocyte-specific functions. Therefore, we expect that Oct4/Sox2-ATMSCs may become a very useful source for hepatocyte regeneration or liver cell transplantation.